Impact of distributed generators on the power loss and voltage profile of sub-transmission network - A.S.O. Ogunjuyigbe (Journal of Electrical Systems and Information Technology, 2016)
This paper presents the impact of distributed generator (DG) on the power loss and voltage profile of sub-transmission network at different penetration levels (PLs). The various DG technologies are modeled based on their electrical output characteristics. Voltage profile index which allows a single value to represent how well the voltage matches the ideal value is developed. The index allows a fair comparison of the voltage profile obtained from different scenarios. The extent to which DGs affect power losses and voltage profile depend on the type of DG technology, PL and the location in which the DG is connected to the grid. The integration of DGs reduces power losses on the network, however, as the PL increases, the power losses begin to increase. A PL of 50–75% is achieved on 69 kV voltage level and 25–50% penetration on 13.8 kV voltage level without an increase in the power loss. Also more DG can be integrated into the network at point of common connection of higher voltage level compared to the low voltage level.